I luoghi della passione. Stadi, culture, comunità: Ferreri, A. (2021). Sugli spalti. In viaggio negli stadi del mondo. Storie di sport, popoli e ribelli. Milano: Meltemi. - Tirino, Mario (Eracle. Journal of Sport and Social Sciences, 2022)
This paper reflects on the stadium as a symbolic place. The “ethnographic” study of stadiums allows us to understand how these structures reflect the social, economic, and cultural processes of cities and nations. Starting from Andrea Ferreri’s book, the paper analyses the role of stadiums in defining the sense of belonging to a community, through the sports stories that take place there. Sporting legends, therefore, are a decisive part of these processes of narration and self-narration, through which individuals and groups recognise themselves as elements of the same shared destiny. This socialising function of stadiums, linked to the multiplicity of experiences, stories, and legends that they “host”, also concerns the rituality of football. As a kind of “universal secular religion” (Boff, 2014), football can connect a community in the name of a (sporting) faith, which consecrates its temples - the stadiums - according to a codified set of ritual gestures, movements, songs, and choruses.